Radio Mobile Assessment of Broadcasting Interference Zones with Unequal D/U Variabilities - Kaschel-Carcamo, H; Cordero-Leiva, S (Institute of Electrical and Electronics Engineers Inc., 2021)
Interference, as well as on any telecommunications network, plays an important role on stablishing the broadcasting frequency plan of a region or a country, being in most cases the available radio spectrum the limit on the number of TV Stations to be installed on a specific area. Upon the increasing on the number of stations, the location of additional terminals becomes an iterative role, needing a friendly tool to perform several simulations to establish or rearrange the plan. This is further increased by the need of assigning different variabilities to the desired and undesired terminals. The freeware Radio Mobile program provides a suitable tool for the purpose, but only for equal variabilities. This work analyses this shortcoming and proposes an easy way to properly calculate the interference with unequal variabilities. Finally, a procedure to correct this problem of coverage calculations with unequal variabilities is presented, providing a correction table to speed up the task. A real case of co-channel interference is also analyzed, this real case corresponds to a station D in C° Orocoipo in Rancagua, VI Region and station U located in C° San Cristobal covering the city of Santiago, Metropolitan Region in Chile. © 2021 IEEE.